Robotic right colectomy with complete mesocolic excision, central vascular ligation and hand-sewn intracorporeal anastomosis: feasibility, safety, and learning curve analysis - Madarasz, Zsolt; Nowakowski, Krysztof; Leitz, Michael; Sturzu, Bogdan-Cornel; Baltamar, Anas; Baginski, Kira; Hoyer, Annika; Hoeppner, Jens; Nimczewski, Fabian; Vladimirov, Miljana (Frontiers in Surgery, 2026)
BackgroundRobotic right colectomy (RRC) with complete mesocolic excision (CME) and central vascular ligation (CVL) has become a standard oncologic approach for right-sided colon cancer. However, evidence regarding hand-sewn intracorporeal anastomosis (ICA) and its associated learning curve remains limited.MethodsThis single-center retrospective study analyzes a series of consecutive patients with histologically confirmed right-sided colon adenocarcinoma who underwent fully robotic RRC with CME, CVL, and hand-sewn ICA. Perioperative outcomes, pathological results, and the learning curves of three colorectal surgeons were evaluated using cumulative sum (CUSUM) and risk-adjusted CUSUM (RA-CUSUM) methods.ResultsOverall, 71 patients were treated by RRC from April 2021 through December 2024. All surgical procedures were completed robotically. The median operative time was 165 min (Q1–Q3: 147–192). Major complications (Clavien–Dindo ≥ IIIb) occurred in 9.9% of cases, with an anastomotic leak rate of 5.6%. Mean lymph-node yield was 29.6 ± 11.2, and R0 resection was achieved in 98.6%. The CUSUM learning curves for the three surgeons revealed a comparable trend, starting with a rise during the learning phase and followed by a decline reflecting increased efficiency. The learning curve plateau was reached after approximately 16 cases for each surgeon.ConclusionRRC with CME, CVL, and hand-sewn ICA is feasible, safe, and oncologically effective. Proficiency is typically achieved after 15–20 cases, supporting its role as a reproducible and teachable procedure in structured robotic colorectal programs.